Penerapan Nilai Piil Pesenggiri bagi Generasi Muda di Era Globalisasi Ditinjau dari Perspektif Sosiologi Hukum - Bagus Putra Setiawan; Febra Anjar Kusuma; Dewi Ayu Nawang; Susilo, Susilo; Erniyanti, Erniyanti (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Piil Pesenggiri is a philosophy of life of the Lampung people that emphasizes self-esteem, honor, and social norms in community life. These values include nemui nyimah (friendliness), nengah nyappur (adaptiveness), sakai sambayan (mutual cooperation), and juluk adek (maintaining dignity). However, globalization and modernization have caused a shift in its application, especially among the younger generation. This study aims to analyze the application of Piil Pesenggiri and the challenges faced from a legal sociology perspective, which includes social norms, social control, customary law, and modernization integration. This study uses a qualitative method with a descriptive approach and thematic analysis of relevant literature. The results of the study indicate that individualism, the influence of social media, and urbanization are the main factors that weaken the application of Piil Pesenggiri values. In addition, the decreasing role of the family and the lack of integration of cultural values in education also accelerate the degradation of this culture. The implications of this study confirm that although the values of Piil Pesenggiri face challenges, these values still have an important role in shaping the identity and social character of the Lampung community. Therefore, preservation strategies such as cultural education, family roles, revitalization of traditions, and the use of digital technology must be implemented so that these values remain relevant and can be passed on to future generations.